2019
DOI: 10.26452/ijrps.v10i2.259
|View full text |Cite
|
Sign up to set email alerts
|

Anti-glycation study of hydro-alcohol and aqueous extracts of Moroccan plant species

Abstract: Inhibition of advanced glycation end products (AGEs) and free radicals generated during diabetes represents a major therapeutic target in the prevention and treatment of diabetic complications. Natural molecules present in fruits, vegetables and herbs and which are usually safe for human consumption, could represent a strong glycation inhibitor. Anti-glycation effect of nine plant species used in traditional medicine has been evaluated after extraction by hot (EAC) or cold (EAF) maceration and by ethanol (EE).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
(27 reference statements)
1
7
0
1
Order By: Relevance
“…Previously [ 23 ], our research group reported PACs (A- and B-types) and flavonol glycosides as the main components of Apollonias barbujana , Laurus novocanariensis (laurel), Ocotea foetens and Persea indica ( Figure 2 ), the most relevant Lauraceae species of Laurissilva. The anti-diabetic effects of similar plants ( Laurus nobilis , Persea americana and Ocotea bullata ) have been documented before [ 3 , 5 , 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and similar properties were expected for targeted Lauraceae species. Therefore, this study was designed to evaluate for the first time the in vitro inhibitory effects of four Lauraceae plant extracts ( A. barbujana , L. novocanariensis , O. foetens and P. indica ) on digestive enzymes linked to the carbohydrates (α-amylase, and α-glucosidase) and lipids metabolism (pancreatic lipase), aldose reductase and protein glycation.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…Previously [ 23 ], our research group reported PACs (A- and B-types) and flavonol glycosides as the main components of Apollonias barbujana , Laurus novocanariensis (laurel), Ocotea foetens and Persea indica ( Figure 2 ), the most relevant Lauraceae species of Laurissilva. The anti-diabetic effects of similar plants ( Laurus nobilis , Persea americana and Ocotea bullata ) have been documented before [ 3 , 5 , 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], and similar properties were expected for targeted Lauraceae species. Therefore, this study was designed to evaluate for the first time the in vitro inhibitory effects of four Lauraceae plant extracts ( A. barbujana , L. novocanariensis , O. foetens and P. indica ) on digestive enzymes linked to the carbohydrates (α-amylase, and α-glucosidase) and lipids metabolism (pancreatic lipase), aldose reductase and protein glycation.…”
Section: Introductionsupporting
confidence: 67%
“…Previously [ 29 , 30 , 39 ], different extracts of L. nobilis prevented the formation of AGEs. Gallic acid was the main compound in the extract and its anti-glycation effect was partially attributed to this phenolic [ 30 ].…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations